Information literacy as an important competency for the 21st century: conceptual approaches - Virkus, Sirje (Journal of the Bangladesh Association of Young Researchers, 2012)
This paper considers information literacy as an important competency for the 21st century. DOI: http://dx.doi.org/10.3329/jbayr.v1i2.10028